Knowledge creation in complex inter-organizational arrangements: understanding the barriers and enablers of university-industry knowledge creation in science-based cooperation. Issue 4 (16th November 2020) - Tootell, Adrian; Kyriazis, Elias; Billsberry, Jon; Ambrosini, Véronique; Garrett-Jones, Sam; Wallace, Gordon
Abstract : Purpose: This study aims to explore the factors undergirding knowledge creation in the university-industry complex inter-organizational arrangement. It builds upon social capital and relationship marketing theories. Design/methodology/approach: This study uses a qualitative research design. In total, 36 innovation champions involved in knowledge creation were interviewed to provide detailed insights into the process. A thematic analysis of the in-depth interviews was conducted. Findings: The principal finding was that opportunistic behavior was a significant barrier to knowledge creation. In severe cases, the knowledge creation process was destroyed, resulting in lost investment. Principled behavior and investment in affect-based and cognition-based trust, through five critical trust development activities, provided the best path to successful knowledge creation. Originality/value: This study contributes to the knowledge management literature by providing insights into the enablers and barriers to the formation of cooperation, a crucial antecedent to knowledge creation literature. It also affords practical implications for innovation managers and policymakers on how they can improve knowledge creation by using social capital and relationship marketing theory in complex inter-organizational arrangements.